2020
DOI: 10.1093/pcp/pcaa066
|View full text |Cite
|
Sign up to set email alerts
|

The SUPPRESSOR of MAX2 1 (SMAX1)-Like SMXL6, SMXL7 and SMXL8 Act as Negative Regulators in Response to Drought Stress in Arabidopsis

Abstract: Abstract Drought represents a major threat to crop growth and yields. Strigolactones (SLs) contribute to regulating shoot branching by targeting the SUPPRESSOR OF MORE AXILLARY GROWTH2 (MAX2)-LIKE6 (SMXL6), SMXL7 and SMXL8 for degradation in a MAX2-dependent manner in Arabidopsis. Although SLs are implicated in plant drought response, the functions of the SMXL6, 7 and 8 in the SL-regulated plant response to drought stress have remained unclear. Here, we performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 92 publications
0
38
0
Order By: Relevance
“…The smxl6smxl7smxl8 triple mutant exhibits significantly induced expression of genes encoding R2R3‐MYB TFs such as PAP1, PAP2, MYB113, and MYB114 which are responsible for the activation of anthocyanin‐biosynthesis genes (e.g., F3'H , DFR , and ANS ). Accordingly, the anthocyanin content is much higher than in wild‐type A. thaliana (Yang et al, 2020; Wang et al, 2020c).…”
Section: Regulation Of the Biosynthesis Of Phenylpropanoid Metabolitesmentioning
confidence: 91%
“…The smxl6smxl7smxl8 triple mutant exhibits significantly induced expression of genes encoding R2R3‐MYB TFs such as PAP1, PAP2, MYB113, and MYB114 which are responsible for the activation of anthocyanin‐biosynthesis genes (e.g., F3'H , DFR , and ANS ). Accordingly, the anthocyanin content is much higher than in wild‐type A. thaliana (Yang et al, 2020; Wang et al, 2020c).…”
Section: Regulation Of the Biosynthesis Of Phenylpropanoid Metabolitesmentioning
confidence: 91%
“…Crosstalks between the ABA pathway and other pathways have been revealed to regulate drought response. For example, SMXLs from SL signaling are negatively involved in drought response by regulating both SL-responsive genes and ABAresponsive genes (Yang T. et al, 2020). Accumulated evidence supports the physical interactions among TFs from ABAdependent and ABA-independent pathways.…”
Section: Crosstalk Between Aba-dependent and Aba-independent Drought Response Pathwaysmentioning
confidence: 95%
“…SUPPRESSOR OF MORE AXILLARY GROWTH2 (MAX2)-LIKE6 (SMXL6), SMXL7, and SMXL8 belonging to SAMX1-LIKE (SMXL) family, in addition to acting as transcriptional repressors in strigolactone signaling, negatively regulate drought response. Transcriptomic and physiological evidence suggested that these three SMXL proteins regulate drought response in both the ABA-dependent and ABAindependent pathways (Wang et al, 2020;Yang T. et al, 2020; Figure 1).…”
Section: Nacs and Other Tf Familiesmentioning
confidence: 99%
“…It was observed that SL signaling mutants are hypersensitive to drought (Zhang et al, 2018). In tomato, even a minute level of SL in roots acts as a systemic signal for aerial tissues under drought stress (Visentin et al, 2016 (Yang, Lian, et al, 2020). Due to the antagonistic nature of CKs, it is speculated that SLs and CKs signaling might be crosstalking for regulating drought tolerance (Li, Herrera-Estrella, & Tran, 2019).…”
Section: Overexpression Of Constitutive Photomorphogenesis (Cop)mentioning
confidence: 99%
“…In a report, max2 mutant exhibits ABA hyposensitivity, thin cuticle, and ultimately compromised drought tolerance, which indicates that MAX2 or SL signaling is involved in positive regulation of drought stress tolerance (Bu et al, 2014; Van Ha et al, 2014). Recently it was reported that suppressors of MAX2 ‐ like (SMXL) 6, 7, and 8 negatively regulate drought tolerance by degrading MAX2 (Yang, Lian, et al, 2020). Due to the antagonistic nature of CKs, it is speculated that SLs and CKs signaling might be crosstalking for regulating drought tolerance (Li, Herrera‐Estrella, & Tran, 2019).…”
Section: Phytohormones Action and Response Mechanism In Drought Stressmentioning
confidence: 99%